How Do Whales See? - Vecino, Elena (2018)
The eyes of two whales Balaenoptera physalus and Baleoptera borealis were studied by our group. In this chapter, we present the anatomical, histological, immunohistochemical and ultrastructural studies of the eyes of both types of whales. Based on the results, we can conclude that at least in these two species, the whales are rod monochromat; their resolution is very limited due to the reduced number of retinal ganglion cells, some of which were giant size (more than 100 micrometers in diameter). The excellent representation of melanopsinic positive retinal ganglion cells suggests an adaptation to the dim light as well as involvement in the circadian rhythms. The large cavernous body located in the back of the eye may provide a mechanism that allows them to move the eye forward and backwords; this may facilitate focusing and provide protection from cold deep-sea temperatures.